INTERPRETING AND UNDERSTANDING THE COMMAND OF GOD: AUTHORITY OF THE SUNNAH AS A SOURCE OF LAW IN THE CASE OF STONING TO DEATH OF A CONVICTED ADULTERER - Mohd Noor, Azman (Jurnal Syariah, 2008)
There is no disagreement among the jurists of all schools of law over the punishment of flogging 100 lashes for zina as prescribed in the Qur’an for ghayr muhsan (unmarried Muslim men and woman convicted of zina).With regards to al-rajm (stoning to death), the majority of jurists hold that the punishment for a convicted married Muslim is stoning to death. The foundation for this ruling is mostly based on the Sunnah as the Qur’an is silent on the provision of such punishment. Nevertheless, besides this mainstream view of the vast Muslim majority, there are varying opinions advocated by the Mu‘tazilites and Kharijites and some contemporary scholars who suggest that the penalty for zina is confined to flogging 100 lashes, and this penalty is uniform regardless of the criminal’s marital background. This paper aims to investigate the efforts made by commentators of al-Qur’an, scholars of hadiths as well as Muslim jurists in the light of the authority of the Sunnah in order to interpret what is intended by the Lawgiver pertaining to the provision of al-rajm. The method used is an analytical and comparative study on the opponents and the advocates of the punishment.